Persepsi Mahasiswa Terhadap Kinerja Dosen Dalam Pembelajaran Dengan Model Block System Learning - Lulu Ulfa Sholihannisa; Hadiansyah Ma’sum (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This research is aimed to know students perception concering to lecturer’s performance in block system learning model. Focus and research subject is students informatics managemen study program in LP3I Polytechnic. This research using quantitavie descrivtive method with likert scale survey questionnaire. The results of this research after analyzing questionnaire data from students with the 200 population an take only 67 as respondent after counting using Slovin formula, that we have known: 1) students experience in learning process we got highest mean score 3.92%; 2) learning plan as lecturer prepared before learning process in questionnaire statement “lecturer prepare and and use learning design on semester (RPS) as guidelines for learning implementation proses” was getting highest mean score 3,79%; 3) in implementation learning that have done by lecturer, was getting highest mean score on 4,01% and lowest mean score on 3.26%; 4) in assessment learning, got mean score on 3.65%; 5) in infrastructures, we got highest mean score on 3.82% and lowest mean score on 3.29% from questionnaire statement of “the classroom and the laboratory capacity is support for getting purpose success leaning; 6) the last components is the use of technology in learning we got mean score 3.37%.